An Update on the Florida State Twin Registry - Taylor, Jeanette E. (2012)
The Florida State Twin Registry began in 2002 through a pilot study of personality disorders and executive cognitive functioning in adult twins. Since 2006, the registry has grown substantially as part of the Learning Disability Research Center at Florida State University that recently began its second funding cycle through the National Institute of Child Health and Development. An update on the Florida State Twin Registry sample, focus, and measures is provided as well as future directions.